2022
DOI: 10.3390/s22145411
|View full text |Cite
|
Sign up to set email alerts
|

A Wi-Fi Indoor Positioning Method Based on an Integration of EMDT and WKNN

Abstract: In indoor positioning, signal fluctuation is one of the main factors affecting positioning accuracy. To solve this problem, a new method based on an integration of the empirical mode decomposition threshold smoothing method (EMDT) and improved weighted K nearest neighbor (WKNN), named EMDT-WKNN, is proposed in this paper. First, the nonlinear and non-stationary received signal strength indication (RSSI) sequences are constructed. Secondly, intrinsic mode functions (IMF) selection criteria based on energy analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This method can reduce the storage overhead and simultaneously improve the positioning accuracy. In [52], an Empirical Mode Decomposition Threshold (EMDT) was proposed to solve the problem of RSSI signal fluctuation. The method first preprocesses the RSSI fingerprint data using the EMDT method and proposes an improved WKNN algorithm, which first obtains the K initial RPs by WKNN, then calculates the center coordinates of the K RPs and the Euclidean distance d ic from each coordinate to the center coordinate.…”
Section: Optimization Based On Database Matching Methodsmentioning
confidence: 99%
“…This method can reduce the storage overhead and simultaneously improve the positioning accuracy. In [52], an Empirical Mode Decomposition Threshold (EMDT) was proposed to solve the problem of RSSI signal fluctuation. The method first preprocesses the RSSI fingerprint data using the EMDT method and proposes an improved WKNN algorithm, which first obtains the K initial RPs by WKNN, then calculates the center coordinates of the K RPs and the Euclidean distance d ic from each coordinate to the center coordinate.…”
Section: Optimization Based On Database Matching Methodsmentioning
confidence: 99%
“…Due to the dynamic nature of the indoor environment, such as the presence and absence of crowds and furniture, as well as variations in temporal and ambient conditions, the signals from the wireless APs fluctuate, causing the RSS measurements to fluctuate, resulting in poor localization accuracy [3], [4]. To deal with the RSS fluctuations, several research works have suggested collecting several RSS measurement observations over a time period and finding the mean average of these observations using techniques such as the mean-averaging filter, moving average filter, median filter, or Kalman filter [5], [6], [7]. During the collection of the time-series RSS observations, it is possible to have RSS outliers [5].…”
Section: Introductionmentioning
confidence: 99%